A Compendium of Information on the Lysosome - Bouhamdani, Nadia; Comeau, Dominique; Turcotte, Sandra (Frontiers in Cell and Developmental Biology, 2021)
For a long time, lysosomes were considered as mere waste bags for cellular constituents. Thankfully, studies carried out in the past fifteen years were brimming with elegant and crucial breakthroughs in lysosome research, uncovering their complex roles as nutrient sensors and characterizing them as crucial multifaceted signaling organelles. This review presents the scientific knowledge on lysosome physiology and functions, starting with their discovery and reviewing up to date ground-breaking discoveries highlighting their heterogeneous functions as well as pending questions that remain to be answered. We also review the roles of lysosomes in anti-cancer drug resistance and how they undergo a series of molecular and functional changes during malignant transformation which lead to tumor aggression, angiogenesis, and metastases. Finally, we discuss the strategy of targeting lysosomes in cancer which could lead to the development of new and effective targeted therapies.